Identifikasi Osteoporosis Berdasarkan Jumlah Percabangan Trabecular Bone Menggunakan Cosfire Filter - Randy Cahya Wihandika, Agus Zainal Arifin, Anny Yuniarti (Politeknik Negeri Madura, 2018)
Mandibular bone is one of the bones that are affected by the reduction of bone mineral density caused by osteoporosis. Therefore, dental panoramic radiographs have been widely used for the identification of osteoporosis. Previous study has shown that the number of branching differs between normal and low bone-mineral-density patients. However, the low contrast level and the presence of noise in the panoramic radiograph images make the extraction of the structure of the trabecular bone to be difficult. Therefore, an enhancement method is required to enhance the structure of the trabecular bone. In this study, a method to detect the trabecular bone branchings with enhancement on the trabecular bone structure using the line operator method is built. From the structure, the location of the branchings is detected using COSFIRE method. The number of the branching is used to ditinguish between the normal radiographs and the radiographs affected by osteoporosis. Evaluation on the classification is performed on 98 images consisting of 41 images in the osteporosis class and 57 images in the normal class. The evaluation results provide sensitivity, specificity, and accuracy of 0,90244, 0,23214, and 0,51546, respectively. The results show that the proposed method gives better performance than the previous method.